Accumulation of Nicotinamide N-Methyltransferase (NNMT) in Cancer-associated Fibroblasts: A Potential Prognostic and Predictive Biomarker for Gastric Carcinoma. (March 2021) - Zhang, Li; Song, Mengmeng; Zhang, Fan; Yuan, Hao; Chang, Wenjun; Yu, Guanyu; Niu, Yongdong
Nicotinamide N -methyltransferase (NNMT), a major metabolic regulator, has been identified as a predictor of cancer prognosis in ovarian and colorectal cancers. The study aims to evaluate the significance of stromal NNMT in gastric cancer (GC). Expression of stromal NNMT in 612 GC and 92 non-malignant tissues specimens was investigated by immunohistochemistry (IHC). The association between NNMT expression and occurrence of cancer or patient outcome was further analyzed, and the factors contributing to disease prognosis were evaluated by multiple Cox models. Stromal NNMT expression was higher in the malignant tissue ( p <0.001). NNMT expression was significantly associated with GC stage ( p =0.006). Compared to stromal "NNMT-low" cases, "NNMT-high" cases has lower disease-specific survival (hazard ratio [HR], 2.356; 95% confidence interval [CI] = 1.591–3.488; p <0.001) and disease-free survival (HR = 2.265; 95% CI = 1.529–3.354; p <0.001), as observed by multivariate Cox analysis after adjusting for stromal NNMT expression with other factors such as tumor grade and size. Notably, patients with stage II NNMT-low GC might be negatively affected by adjuvant chemotherapy, but lower stromal NNMT expression predicted a more favorable prognosis for GC. Our study confirmed that stromal NNMT expression is significantly increased in GC, which predicts an unfavorable post-operative prognosis for GC: